Understanding the Relationship between Distress Behaviour and Health Status of People with Autism Spectrum Disorder - Koceski, Antonio; Smith, Callum J.; Syed, Yasir Ahmed; Trajkovski, Vladimir (MDPI AG, 2023)
Autism Spectrum Disorder (ASD) is associated with complex distress and challenging behaviours that have a negative impact on the everyday life of those with ASD, as well as their parents and carers. These challenging behaviours include negative emotional behaviours, motor behaviours, and changes in routines. Even though challenging behaviours occur in most subjects with ASD, the cause of these largely remains unknown. It has been implicated that these challenging behaviours are associated with a change in the health of those with ASD. More research needs to be conducted that can establish a direct association. Towards this goal, the present study aimed to explore whether health status had an impact on the distressing behaviour in the subjects diagnosed with ASD. We analysed the response from the parents/carers in a Macedonian population of those with ASD, to determine which challenging behaviours were most likely to be observed during a change in health. Based on a scoring system, the manifestation of challenging behaviour was evaluated and compared with the changes in health. Changes in appetite or dietary preferences, irritability and low mood, and loss of previously acquired skills had the greatest association with a change in health. These findings provide early insight into types of challenging behaviours that are directly associated with a change in health. Our results demonstrate a relationship between health status and challenging behaviour in the subject with autism, suggesting that caregivers may need to consider this when choosing strategies for managing challenging behaviour.
Keywords: Autism Spectrum Disorder; challenging behaviour; social deficits; diet; health status